Religiosity, Attitude Toward Business, and Ethical Beliefs: Hispanic Consumers in the United States - Patwardhan, Abhijit M. (Journal of business ethics, 2012)
Growth of the Hispanic consumer population in America is changing the marketplace landscape. Due to their considerable buying power, a better understanding of Hispanic consumer behavior has become a necessity. The marketing literature has examined issues regarding religiosity and attitude toward business in regards to consumer ethical beliefs as well as research differentiating consumers on the basis of ethnicity due to their inherently different religious principles. Therefore, the present study contributes to the existing consumer ethics literature by examining the roles of religiosity and attitude toward business in determining consumer ethical beliefs. Furthermore, this study compares the relationships among religiosity, attitude toward business, and ethical beliefs at the sub-cultural level (i.e., between Hispanic and Anglo-American consumers). Survey data compare a sample of 187 predominately Catholic Hispanic consumers with a sample of 127 predominately protestant Anglo consumers. Results suggest a positive relationship between intrinsic religiousness and beliefs that questionable consumer activities are unethical. However, extrinsic religiousness does not impact consumer views as to the ethicality of consumer practices. Hispanics exhibit higher levels of extrinsic religiousness than Anglos, but no difference in terms of their intrinsic religiousness. Results also suggest that Hispanics have a more negative attitude toward business than Anglos do. Implications of these results are discussed.